Social and economic development and pregnancy mental health: secondary analyses of data from rural Vietnam - Ruby Stocker; Trang Nguyen; Thach Tran; Ha Tran; Tuan Tran; Sarah Hanieh; Beverley-Ann Biggs; Jane Fisher (BMC Public Health, 2020)
Abstract Background This study aimed to establish whether changes in the socioeconomic context were associated with changes in population-level antenatal mental health indicators in Vietnam. Methods Social, economic and public policies introduced in Vietnam (1986–2010) were mapped. Secondary analyses of data from two cross-sectional community-based studies conducted in 2006 (n = 134) and 2010 (n = 419), involving women who were ≥ 28 weeks pregnant were completed. Data for these two studies had been collected in structured individual face-to-face interviews, and included indicators of antenatal mental health (mean Edinburgh Postnatal Depression Scale Vietnam-validation (EPDS-V) score), intimate partner relationships (Intimate Bonds Measure Vietnam-validation) and sociodemographic characteristics. Socioeconomic characteristics and mean EPDS-V scores in the two study years were compared and mediation analyses were used to establish whether indicators of social and economic development mediated differences in EPDS-V scores. Results Major policy initiatives for poverty reduction, hunger eradication and making domestic violence a crime were implemented between 2006 and 2010. Characteristics and circumstances of pregnant women in Ha Nam improved significantly. Mean EPDS-V score was lower in 2010, indicating better population-level antenatal mental health. Household wealth and intimate partner controlling behaviours mediated the difference in EPDS-V scores between 2006 and 2010. Conclusions Changes in the socioeconomic and political context, particularly through policies to improve household wealth and reduce domestic violence, appear to influence women’s lives and population-level antenatal mental health. Cross-sectoral policies that reduce social risk factors may be a powerful mechanism to improve antenatal mental health at a population level.